Effect Of Alpha-Tocopherol On Spermatozoa Death Of Apoptosis and Necrosis in Rats (Rattus Norvegicus) Exposed 2,3,7,8- Tetrachlorodibenzo-P-Dioxin - Valderama Gomang (Stem Cell Research and Development Center, Universitas Airlangga, 2021)
The aims of this research was to investigate effect of alpha-tocopherol on spermatozoa death in form of apoptosis and necrosis in rats (Rattus norvegicus) exposed 2,3,7,8- tetrachlorodibenzo-p-dioxin. Male rats were administered TCDD and alpha-tocopherol in experimental groups. Five experimental groups of a combination of TCDD and alpha- tocopherol were designed as follows; 0.5 ml of corn oil (control negative group, K-), 700 ng/kg/d of TCDD and 0.5 ml of corn oil (treatment control), 700 ng/kg/d of TCDD and 77 ng/kg/d of alpha-tocopherol (Group P1), 700 ng/kg/d of TCDD and 140 mg/kg/d of alpha-tocopherol (Group P2), 700 ng/kg/d of TCDD and 259 mg/kg/d of alpha- tocopherol (Group P3) respectively. Alpha-tocopherol and TCDD were given by oral gavage for 20 days. The result indicated that TCDD increased spermatozoa death in form of apoptosis and also necrosis. Alpha-tocopherol at 259 mg/kg/d most effective to decreased spermatozoa death number. The conclusion indicated that alpha-tocopherol at 259 mg/kg/d effective to decreased the spermatozoa death in form of apoptosis and necrosis in rats (Rattus norvegicus) exposed 2,3,7,8-tetrachlorodibenzo-p-dioxin.